When work–family guilt becomes a women's issue: Internalized gender stereotypes predict high guilt in working mothers but low guilt in working fathers - Aarntzen, Lianne; Derks, Belle; van Steenbergen, Elianne; van der Lippe, Tanja (British Journal of Social Psychology, 2023)
Les stéréotypes de genre prescrivent aux mères, mais pas aux pères, de donner la priorité à leur famille plutôt qu’à leur travail. Par conséquent, l’intériorisation des stéréotypes de genre peut prédire une culpabilité plus élevée chez les mères que chez les pères dans des situations où ils privilégient leur travail plutôt que leur famille. L’étude 1 (135 mères et 116 pères) a en effet révélé que plus les stéréotypes de genre implicites des pères étaient forts (mesurés à l’aide d’une tâche d’association implicite genre-carrière), moins les pères se déclaraient coupables dans une situation fictive d’interférence du travail dans la famille. Bien que les mères aient en moyenne déclaré une culpabilité plus élevée que les pères, cet effet n’a pas été atténué par leurs stéréotypes de genre implicites. L’étude 2 (étude du journal quotidien auprès de 105 mères) a toutefois révélé des preuves de l’effet modérateur des stéréotypes de genre implicites sur la culpabilité des mères qui travaillent. Plus les stéréotypes de genre implicites des mères étaient forts, plus elles déclaraient avoir des conflits entre le travail et la famille et de la culpabilité les jours où elles travaillaient de longues heures. Ces résultats montrent que les stéréotypes de genre implicites façonnent la façon dont les parents perçoivent leurs choix travail-famille.
Keywords: 2000 à aujourd'hui; 2020-2029; care; charge mentale; conciliation famille-travail; culpabilité; discipline; europe; famille; maternité; pays-bas; projet charge mentale; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; émotions

Articulation famille-travail : exploration auprès de mères pratiquant le travail du sexe - Deslauriers, Annick (Université du Québec à Montréal, 2023)
Malgré l’entrée massive des femmes sur le marché du travail et les avancées que l’on doit aux mouvements féministes, le patriarcat demeure un paradigme dominant à l’égard de la question familiale (Descarries et Corbeil, 2002ª). Dans sa version plus contemporaine, le consensus social concernant la famille est aussi imprégné de l’influence de l’épidémiologie sociale, un paradigme qui supporte une ambition scientiste et normative (Parazelli et al., 2003 et Parazelli, 2013). Comme la mère porte implicitement la responsabilité de l’ordre familial et par extension, de l’ordre social, cette normativité est étroitement liée au genre (Cardi, 2007; 2010 et 2015). Cette recherche s’ancre dans les épistémologies féministes. Elle propose une démarche qualitative, exploratoire et critique en s’intéressant à la réalité des mères qui pratiquent le travail du sexe à partir de l’idée selon laquelle « on ne peut être mère et putain à la fois » (Ovidie, 2018). Le stéréotype de la mère s’oppose effectivement à celui de la putain dans l’imaginaire social (Descarries et Mathieu, 2009). Les mères qui pratiquent le travail du sexe doivent ainsi réconcilier leur posture d’être humain discrédité en regard de leur travail et leur identité de mère, laquelle est soumise à des injonctions normatives de plus en plus élevées (Samtani et Trejos-Castillo, 2015). Nous exposons les données issues d’entrevues semi-dirigées réalisées auprès de huit mères exerçant le travail du sexe afin d’explorer leur expérience de l’articulation famille-travail. Cette expérience est traversée par la gestion des temps et des espaces de la vie familiale et du travail, laquelle relève surtout de la mobilisation de stratégies personnelles par les mères. Ces constats correspondent aux connaissances portant sur l’articulation famille-travail (Descarries et Corbeil 2002ᵇ; Malenfant, 2002; Tremblay, 2003 et Seery, 2014 et 2020). S’agissant des mères que nous avons rencontrées, cette expérience a cependant de particulier qu’elles doivent composer avec le stigmate de putain (Pheterson, 2001). Nous avons donc recours à certains travaux portant sur la stigmatisation symbolique et structurelle aux fins d’analyse et de discussion de nos résultats de recherche. On relève deux grands types de stratégies employées par ces femmes pour faire face au stigmate de putain : elles s’en distancient ou elles lui résistent. La valorisation dans le travail compte parmi les stratégies de résistance. À ce sujet, elles énoncent des réalités et des compétences se rapportant au travail du care. Ainsi, la perspective du care est également mobilisée dans notre cadre conceptuel. Nous réfléchissons notamment au travail du sexe comme travail du care à la lumière des concepts de travail émotionnel (Hochschild, 2003 et 2012), de sale boulot (Lhuilier, 2005 et Molinier 2011) et de défenses collectives féminines et viriles (Molinier, 2000; 2002 et 2004), alors qu’une part importante du travail du care demeure stigmatisée en tant que sale boulot (Molinier, 2011) et que le travail émotionnel est sous-pesé dans l’appréhension de la valeur du travail du care (Molinier, 2011 et 2020). De plus, bien que la dimension du care soit transversale aux activités de soins et de services aux personnes, elle est généralement occultée du sexuel (Molinier, 2009 et 2011). Ces idées nous permettent d’éclairer le discrédit porté à l’endroit des mères pratiquant le travail du sexe et de réfléchir à leurs avenues de reconnaissance et de citoyenneté. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : travail du sexe, mères, articulation famille-travail, féminisme, patriarcat, imaginaire social, discours sociaux dominants, significations imaginaires sociales, stigmatisation, stigmate de putain, travail du care, travail émotionnel, sale boulot, défenses collectives
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; canada; care; conciliation famille-travail; discipline; famille; patriarcat; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail; travail du sexe; travail social

La charge mentale et l'anxiété qui en découle - Spill the Tea (2023)
Aujourd’hui, on jase avec vous de la charge mentale et de tout se qui en découle. Ne nous faisons pas de cachette, le rôle de maman apporte une énorme charge mentale pour la plupart d’entre nous et nous avions envie de s’ouvrir sur le sujet. On espère que l’épisode saura vous apaiser et vous montrer que vous n’êtes pas seules.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; anxiété; charge mentale; conciliation famille-travail; famille; maternité; projet charge mentale; périodes historiques; québec; régions géographiques; santé; santé mentale des mères; thématiques; travail

The COVID-19 pandemic and the gender gap in newly created domains of household labor - Abromaviciute, Jurgita; Carian, Emily K. (Sociological Perspectives, 2022)
In this study, we draw on interview data from 62 matched different-sex, dual-career spouses raising young children to examine the mechanisms behind the gender gap in household labor during the COVID-19 pandemic. We argue that the pandemic represents a unique case of social uncertainty and an opportunity to observe how structural conditions shape the gendered division of household labor. We find that under the rapid social transformation imposed by the pandemic, gender serves as an anchor and orienting frame for couples with young children. We argue that the pandemic (1) expanded traditional gender expectations to new domains of household labor and (2) heightened the importance of gendered explanations for the division of labor that justified intra-couple inequality. Our findings suggest that the particular structural conditions that characterize different times of uncertainty work through slightly different mechanisms, yet produce the same outcome: gender inequality, with long-lasting and wide-ranging implications. © The Author(s) 2022.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; care; charge mentale; conciliation famille-travail; discipline; division sexuelle du travail; famille; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique; états-unis

"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

Women's overload during the pandemic: Unpaid care work, financial well-being, and stress - Bulog, Ivana; Pepur, Sandra; Smiljanić, Ana Rimac (Management : Journal of Contemporary Management Issues, 2022)
This study examines the relationship between unpaid care work, financial well-being, and stress levels among women during the COVID-19 pandemic. The pandemic caused downturns in the economies of countries worldwide and led to uncertainties and changes that created conditions for increased stress levels and consequently impaired well-being. In addition to social distancing and lockdown measures to cope with the virus, working from home, home schooling, caring for sick and older family members, and financial problems have added burdens and have proven to be additional personal and family stressors. The findings are based on an online survey conducted among women during the second lockdown in Croatia. Additional unpaid care work and lower financial well-being affect the increased stress felt by women during the pandemic. This is especially pronounced among women who are more involved in paid work. During the pandemic, additional unpaid care work, increased involvement in paid work, and jeopardized financial well-being were stressors for women. Our results indicate the importance of women s free time for their own and their families 'well-being.
Keywords: 2000 à aujourd'hui; 2020-2029; anxiété; care; conciliation famille-travail; covid-19; croatie; discipline; europe; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; sciences de la gestion; thématiques; travail; travail gratuit; économie

COVID-19 and gender inequity in science: Consistent harm over time - Caldarulo, Mattia; Olsen, Jared; Frandell, Ashlee; Islam, Shaika; Johnson, Timothy P; Feeney, Mary K; Michalegko, Lesley; Welch, Eric W (PLoS One, 2022)
Stay-at-home-orders, online learning, and work from home policies are some of the responses governments, universities, and other institutions adopted to slow the spread of COVID-19. However, research shows these measures have increased pre-existing gender disparities in the workplace. The working conditions for women during the pandemic worsened due to increased family care responsibilities and unequal distribution of domestic labor. In the academy, working from home has resulted in reduced research time and increased teaching and family care responsibilities, with a larger proportion of that burden falling to women. We investigate the persistence of gender inequity among academic scientists resulting from university COVID-19 responses over time. We draw on two surveys administered in May 2020 and May 2021 to university-based biologists, biochemists, and civil and environmental engineers, to analyze how the pandemic response has disproportionately impacted women in academia and the endurance of those inequities. Results show significantly greater negative impacts from the pandemic on women’s research activities and work-life balance, compared to men. We conclude by discussing the implications of our results, and the need for the academy to better predict and adjust to the gender disparities its policies create.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; conciliation famille-travail; covid-19; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail gratuit; états-unis

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

Les effets de la crise sociosanitaire de la COVID-19 sur la charge mentale des femmes : le vécu de travailleuses de la région de Chaudière-Appalaches. Synthèse - Seery, Annabelle; Forest, Danielle; St-Germain, Lise (Trois-Rivières: Centre de recherche sociale appliquée (CRSA), 2022)
Fiche synthèse 1. Objectifs Intentions : Le but de cette recherche est de «documenter l’impact de la crise sociosanitaire sur la charge mentale des travailleuses de la région [de la Chaudière-Appalaches].» (p. 3) 2. Méthode Échantillon/Matériau : L’échantillon est constitué de 22 femmes résidentes de Lévis, âgées entre 26 et 45 ans. La majorité de ces femmes «occupe un emploi à temps plein et a travaillé au moins une partie de la 1re année de pandémie en télétravail.» (p. 4) De plus, la majorité des participantes habitent avec leur partenaire et ont des enfants.» (p. 4) Instruments : Guide d’entretien semi-directif Type de traitement des données : Analyse de contenu 3. Résumé Les résultats montrent que «[l]a fermeture des écoles et des services de garde de même que la diminution du soutien disponible ont entrainé une augmentation de la charge de travail des femmes au sein de leur famille.» (p. 6) Les résultats révèlent également que «[l]es femmes sont demeurées les responsables du travail à réaliser dans la famille, en plus de voir s’ajouter la responsabilité de l’école à la maison ou le casse-tête de la garde des enfants. [De plus], [l]es femmes proches aidantes ont aussi vu leur charge de travail augmentée en répondant aux besoins de leurs proches dépendants.» (p. 6) Aussi, «[l]es femmes qui ont fait du télétravail ont rencontré plusieurs difficultés à cause du contexte particulier dans lequel elles ont dû travailler (notamment avec les enfants à la maison).» (p. 6) Enfin, les résultats mettent en lumière que «[l]es mères, et encore plus celles ayant des enfants de moins de cinq ans, vivent davantage de détresse psychologique que les pères. La détresse psychologique est aussi plus élevée chez les parents moins aisés financièrement.» (p. 6) Mots-clés charge mentale (5) Chaudière-Appalaches (68) conciliation famille-travail (640) COVID-19 (112) division sexuelle du travail (21) mère (1459) télétravail (16) travail domestique (145)
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; charge mentale; conciliation famille-travail; covid-19; division sexuelle du travail; famille; projet charge mentale; périodes historiques; québec; régions géographiques; santé; santé des travailleuses; thématiques; travail; travail domestique

The entrenchment of the ideal worker norm during the COVID-19 pandemic: Evidence from working mothers in the United States - Zanhour, Mona; Sumpter, Dana (Gender, Work and Organization, 2022)
We study shifts in the ideal worker culture as experienced by working mothers across organizations in the United States during the COVID-19 pandemic. Experiences of 53 interviewees who attended to increased responsibilities across both work and family domains revealed an entrenchment of the ideal worker culture across nearly all organizations and professions. This manifested in three levels: as (1) a reinforced ideal worker culture in the workplace through work intensification, increased competitiveness, and surface-level support; (2) the reinforcing of organizations' ideal worker norms at home, with gendered division of space and labor; and (3) experienced internalized ideal worker norms in the expectations working mothers maintained for themselves. These findings offer insight into the lives of working mothers during the COVID-19 pandemic and the challenges which have pushed many mothers to reduce work hours or leave the workforce. Highlighting the intricate nature of the entrenchment of the ideal worker culture informs implications for theory of gendered organizations and for organizational practice. © 2022 John Wiley & Sons Ltd.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; conciliation famille-travail; culpabilité des mères; famille; maternité; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail; travail des mères; états-unis

Paid and unpaid work during the Covid-19 pandemic: A study of the gendered division of domestic responsibilities during lockdown - Borah Hazarika, Obja; Das, Sarmistha (Journal of Gender Studies, 2021)
The Covid-19 pandemic and the strategies implemented to deal with it have had economic and societal repercussions all over the world. In India, a nationwide lockdown was initiated on 25 March 2020 which continued in a diluted form as we were conducting the interviews for the paper in July 2020. The lockdown brought activities outside the home to a standstill and people were expected to stay indoors in order to ensure social distancing and break the chain of infection. The lockdown sparked its own problems and triggered discussions on issues including economic hardship and domestic violence. The question of how domestic responsibilities are shared among adults in families has also come to the forefront of debate. As hired part-time help was discontinued under lockdown, parents who had hitherto outsourced childcare and housework were suddenly left to fend for themselves. This article attempts to explore the manner in which such unpaid domestic responsibilities, especially childcare, were shared between parents in middle-class homes. The gendered nature of this division of housework and care work, and its varied implications on the paid work and careers of mothers and fathers, is the focus of inquiry. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2020-2029; asie; conciliation famille-travail; confinement; covid-19; discipline; division sexuelle du travail; famille; inde; pandémie; projet charge mentale; périodes historiques; régions géographiques; science politique; science politique et droit; soins aux enfants; thématiques; travail; travail domestique

Return of the 1950s housewife? How to stop coronavirus lockdown reinforcing sexist gender roles - Chung, Heejung (2020)
Alors que le virus COVID-19 se propage à travers le monde, de nombreux gouvernements ont fermé les écoles , les crèches et autres établissements de garde d'enfants. Avec de plus en plus de personnes travaillant à domicile , il est probable que de nombreuses familles se retrouveront dans une situation où les deux parents essaient de travailler depuis la table de la cuisine tout en essayant de faire l'école à la maison aux enfants . En plus des tâches ménagères habituelles, comme la cuisine et le ménage, ces tâches peuvent représenter une charge supplémentaire pour de nombreux parents à l'heure actuelle. Il est cependant probable que même si les deux parents sont désormais à la maison, une grande partie des tâches « domestiques » reposera toujours sur les épaules des femmes de la maison. Tout comme la ménagère des années 1950, les femmes devront non seulement préparer des repas savoureux, garder la maison propre et bien rangée et divertir les enfants, mais elles devront également faire tout cela tout en travaillant à domicile.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; charge mentale; conciliation famille-travail; covid-19; discipline; famille; pandémie; projet charge mentale; périodes historiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

The COVID-19 pandemic has increased the care burden of women and families - Power, Kate (Sustainability: Science, Practice and Policy, 2020)
While women were already doing most of the world’s unpaid care work prior to the onset of the COVID-19 pandemic, emerging research suggests that the crisis and its subsequent shutdown response have resulted in a dramatic increase in this burden. It is likely that the negative impacts for women and families will last for years without proactive interventions. What we commonly refer to as “the economy” would not function without the (often unrecognized) foundation of work provided by the “care economy”: the reproduction of everyday life through cooking, raising children, and so forth. The paid economy has slowed not only because people are physically not allowed into workplaces, but also because many families currently need to raise and educate their children without institutional support, which is reducing remunerated working hours and increasing stress. It has long been recognized that gross domestic product ignores the care economy and heterodox economists have promoted alternative economic systems that could value care work and facilitate a fairer sharing of domestic labor while promoting environmental and economic sustainability. This policy brief builds on recent work on the care economy to explore implications of the COVID-19 pandemic and opportunities for addressing the burden of unpaid care work.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; care; covid-19; famille; genre; périodes historiques; ressource en ligne; thématiques; travail

La conciliation travail famille études (CTFE) en temps de pandémie - Development, PodBean
Nous écoutons Sylvie Lévesque, directrice de la Fédération des associations de familles monoparentales et recomposées du Québec et Mélanie Lefrançois, professeure en santé et sécurité du travail au Département d’organisation et ressources humaines de l’École des sciences de la gestion à l’UQAM.
Keywords: 2000 à aujourd'hui; 2020-2029; amérique du nord; amériques; approches et analyses; canada; conciliation famille-travail; cours; discipline; famille; inégalités; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail